2013
DOI: 10.1007/s11010-013-1918-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of postischemic cardiac contractile dysfunction by CaMKII inhibition: effects on programmed necrotic and apoptotic cell death

Abstract: While Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) has been suggested to be an important protein regulating heart function upon ischemia/reperfusion (I/R), the mechanisms responsible are not fully known. Furthermore, it is not known whether CaMKII activation can modulate necroptosis, a recently described form of programmed cell death. In order to investigate these issues, Langendroff-perfused rat hearts were subjected to global ischemia and reperfusion, and CaMKII inhibition was achieved by adding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
3
34
0
2
Order By: Relevance
“…It can be mentioned that this axis of RIP3-dependent necroptosis was found in both I/R and doxorubicin-induced cardiotoxicity [13], animal model analogues to types of heart failure referred to in our study. The involvement of this protein kinase, a key regulator of Ca 2+ homeostasis in cardiomyocytes in myocardial I/R-induced necroptosis, has also been proposed in our recent study showing that the inhibition of CaMKII reversed certain changes in pronecroptotic markers what was accompanied by improved contractile function [10]. It should be noted, however, that the pronecroptotic axis involving RIP3-CaMKII resulting in cell death via effects on mitochondria [13] is contradictory to studies showing that necroptosis occurs due to plasma membrane disruption as a consequence of recruitment of MLKL following RIP1-RIP3 activation [7, 12, 20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be mentioned that this axis of RIP3-dependent necroptosis was found in both I/R and doxorubicin-induced cardiotoxicity [13], animal model analogues to types of heart failure referred to in our study. The involvement of this protein kinase, a key regulator of Ca 2+ homeostasis in cardiomyocytes in myocardial I/R-induced necroptosis, has also been proposed in our recent study showing that the inhibition of CaMKII reversed certain changes in pronecroptotic markers what was accompanied by improved contractile function [10]. It should be noted, however, that the pronecroptotic axis involving RIP3-CaMKII resulting in cell death via effects on mitochondria [13] is contradictory to studies showing that necroptosis occurs due to plasma membrane disruption as a consequence of recruitment of MLKL following RIP1-RIP3 activation [7, 12, 20].…”
Section: Discussionmentioning
confidence: 90%
“…In fact, cleavage of RIP1 and RIP3 by caspase-8 prevents necroptotic signaling while simultaneously promoting apoptosis [6]. The importance of necroptosis has been shown mainly in non-cardiac pathologies [9] and recently, it has also been demonstrated in rodent reperfused hearts subjected to previous acute global and regional ischemia [10, 11] as well as in a model of cardiomyopathy [12, 13]. Relevance and proposed mechanisms of necroptotic cell death in heart failure have been reviewed elsewhere [14].…”
Section: Introductionmentioning
confidence: 99%
“…More important is the ratio of pro-to anti-apoptotic proteins in a cell [23]. In this regard, Bcl-2 is an anti-apoptotic factor, whereas Bax is a pro-apoptotic factor, and the Bcl-2/Bax ratio is recognized as an index of intrinsic pathway activation [24,25]. We believe that the increased Bcl-2/Bax ratio in the BDL-mice reflects an anti-apoptotic compensatory reaction in the intrinsic pathway in reaction to the net pro-apoptotic imbalance mediated by the extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In line, a recent study has suggested that RIP3, being a downstream target of RIP1, activates CaMKII (Zhang et al 2016) which is known to phosphorylate and thus regulate excitation-contraction coupling of the heart (Luo et al 2013). The link between CaMKII, RIPs, necroptotic cell death and the force of contractile function has been proposed for the first time by our group (Szobi et al 2014). In fact, we have found that inhibition of CaMKII normalizes the upregulation of RIP1 levels and that these changes are linked with the improved contraction cycle in I/R heart.…”
mentioning
confidence: 51%